Rare presentation on Meckels diverticulum on the mesenteric border forming a mass - Ahmad, Zeeshanuddin; Sharma, Apoorv; Vatti, Vikram; Ahmed, Minhajuddin; Ali, Manal Ashraf (International Surgery Journal, 2016)
Meckel’s diverticulum (MD) is a diagnostic and surgical challenge. Majority of Meckel’s diverticulae are silent and are discovered incidentally intraoperatively. Mostly, they are located at antimesentric border of distal ileum. Herein, we present a case a mesenteric sided MD 44 cm from ileocecal junction that had formed a mass, without obstructing the lumen of ileum. A segmental resection was done with adequate margin and ileum was reanastomosed. Histopathology of the specimen confirmed chronic inflammation of MD. Post-operative period was uneventful, and the patient was discharged in a stable condition.